Speech Function in the “Moxie” Movie Sociolinguistics Study - Widya Novia Damayanti; Meita Luckitawati Sujatna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the types of speech functions that exist in "Moxie" movie and also to determine the purpose of the speech function used by the characters in the film when the characters are having conversations. The source of this research data taking from the "Moxie" movie. The results of this study obtained the results of 227 utterances contained in the speech function from the dialogue movie, and the data was classified into four: 78 Statement (34,4%), 106 Questions (46,7%), 16 Offer (7%) and command 27 (11,9%). The most dominant type of speech function used in the film "Moxie" is questions 106 (46,7%), it can be seen that in the film there are many conversations related to question because the characters in the film use a lot of questions when having conversations. The purpose of speech function in the “Moxie” movie by using the types speech function so that the speaker and listener can communicate well, communication to make the listener understand the speaker's mean.